2015
DOI: 10.1109/tbme.2015.2428636
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Effects of Stiffness in Parallel With the Knee Joint During Walking

Abstract: The human knee behaves similarly to a linear torsional spring during the stance phase of walking with a stiffness referred to as the knee quasi-stiffness. The spring-like behavior of the knee joint led us to hypothesize that we might partially replace the knee joint contribution during stance by utilizing an external spring acting in parallel with the knee joint. We investigated the validity of this hypothesis using a pair of experimental robotic knee exoskeletons that provided an external stiffness in paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…However, a change in knee kinematics and kinetics as a result of motorized assistance may affect the accuracy of our estimation models. During walking in able-bodied individuals with an assistive exoskeleton that provided external stiffness to the knee joint, Shamaei et al found that the combined dynamic stiffness of the knee and device remains invariant when the external assistive stiffness is provided up to ~80% of the internal knee stiffness [21]. Their finding, combined with the strong performance of our estimation models across a reasonably wide range of knee angles, provides confidence in the ability our proposed approach to accurately determine the internal knee moment when motorized assistance may result in altered kinematics while treating crouch gait.…”
Section: Discussionmentioning
confidence: 99%
“…However, a change in knee kinematics and kinetics as a result of motorized assistance may affect the accuracy of our estimation models. During walking in able-bodied individuals with an assistive exoskeleton that provided external stiffness to the knee joint, Shamaei et al found that the combined dynamic stiffness of the knee and device remains invariant when the external assistive stiffness is provided up to ~80% of the internal knee stiffness [21]. Their finding, combined with the strong performance of our estimation models across a reasonably wide range of knee angles, provides confidence in the ability our proposed approach to accurately determine the internal knee moment when motorized assistance may result in altered kinematics while treating crouch gait.…”
Section: Discussionmentioning
confidence: 99%
“…Physical testing requires the design and fabrication of prototypes, which can be time-consuming and expensive, and may require several design iterations to refine key device parameters [ 33 ]. A central requirement is to minimize the mass added to the leg [ 23 , 34 ], particularly of the components attached most distally [ 24 ]. Minimizing distal mass can require special accommodation at the design stage (e.g., by mounting a spring in a backpack and transmitting force to the knee using a Bowden cable [ 30 ]) and can increase the cost of components (e.g., by fabricating selectively reinforced carbon fiber frames for each subject [ 25 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Exoskeleton mass and inertia have a significant effect on the metabolic cost of the user. This is exactly why minimizing them should be one of the main objectives in exoskeleton design [112]. Research for the knee joint has shown that the effects of added inertia on the kinematics of gait were significantly bigger than those of misalignment [52].…”
Section: Misalignment Compensation Abilitymentioning
confidence: 99%